Analisis Kuantitatif Strategi Pemasaran Tiktok dalam Meningkatkan Brand Awareness UMKM Swara - Annisa Aprilia; Amalia Amalia (DBESTI: Journal of Digital Business and Technology Innovation, 2026)
TikTok is one of the most engaging digital platforms for marketing, particularly among the younger generation. UMKM Swara, a small business in the custom fashion sector, has utilized TikTok as a platform for digital marketing. However, in practice, it still faces challenges in attracting audience attention and maintaining consistency in content planning. This study aims to implement and recommend effective TikTok marketing strategies for UMKM Swara. A quantitative approach was used, with data collected through observation, interviews, and questionnaires distributed to UMKM Swara's TikTok audience. The analysis employed simple linear regression. The results show that TikTok marketing strategies have a significant impact on increasing UMKM Swara's brand awareness, with a regression coefficient of 0.432 and a significance value of 0.001. Classical assumption testing also confirmed that the regression model used is valid and free from bias. The R² value of 0.441 indicates that 44.1% of the variation in brand awareness can be explained by the TikTok marketing strategy. Therefore, creative and interactive content-based marketing strategies on TikTok are proven effective in enhancing UMKM Swara’s brand awareness.